The faculty of philosophy: history of formation - Rumyantseva, Tatsiana G. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
A brief history of the formation of the faculty of philosophy within the walls of a classical European university is shown; defined the mission that it traditionally performed in the European education system, embodying the principle of the unity of science and the formation of a complete picture of the world. Analyzed the impact on the formation of a classical European university, of German classical philosophy in the face of its main representatives – I. Kant, I. Fichte, F. Schelling and G. Hegel, who left a number of brilliant works dedicated to understanding the essence of university education and the place in it of the faculty of philosophy. The role and tasks of philosophy and philosophical education in the modern university system, their role in preserving the spiritual and moral culture and ensuring the innovative development of society are also revealed, which is possible only with a meaningful understanding of the challenges that society faces today.
Keywords: faculty of philosophy; types of the faculty of philosophy; faculties of philosophy at the Jena and Berlin Universities; I. Kant; I. Fichte; J. Ortega-i-Gasset; K. Jaspers; goal and objectives of the philosophy and philosophy department in the era of global challenges